2022 International Conference on Machining, Materials and Mechanical Technologies - Chen, Yi Cheng; Lin, Li-Gang; Yamada, Keiji (Trans Tech Publications Ltd, 2024)
This edition contains articles that were presented at the 4th International Conference on Machining, Materials and Mechanical Technologies (IC3MT 2022, Taipei, Taiwan, 11-14 November 2022) which address the latest developments in materials science, nanomaterials and nanotechnologies, coatings and surface treatment procedures, as well as metal processing technologies and engineering solutions in the design of machines and mechatronics systems. The publication will be helpful to specialists in mechanical engineering. Nanomaterials, Nanoprocessing, Coating, Surface Treatment, Steel, Composite, Electropolishing, Mechanical Properties, Single Point Incremental Sheet Forming, Friction Welding, Drilling, Cutting, Burnishing, Fatigue Analysis, Tool, Machine, Mechatronics, Hydrostatic Bearing, Machine Measurement Materials Science, Mechanical Engineering, Manufacturing.